ARMENIAN-CHINESE RELATIONS IN THE CONTEXT OF CHINA'S FOREIGN ECONOMIC POLICY - Arman Arzuman Harutyunyan (International Journal of Innovative Technologies in Social Science, 2024)
Armenian-Chinese economic relations encompass several key components that reflect both the evolution of bilateral ties and China's broader global economic strategy. These relations are significantly shaped by China's "One Belt, One Road" initiative, which offers Armenia various investment opportunities and economic benefits. However, the relationship is not one-sided. Both countries are actively working to enhance their trade relations, demonstrating consistent growth. They have the potential to explore new markets and further develop their economic connections. This article discusses the directions and opportunities for advancing Armenia-China relations and presents specific approaches and measures to stimulate development.